АЛГОРИТМ РЕАГУВАННЯ НА НАДЗВИЧАЙНІ СИТУАЦІЇ ІЗ ЗАСТОСУВАННЯМ БЕЗПРОВОДОВИХ СЕНСОРНИХ МЕРЕЖ - Хоменко, Євгеній Олексійович (Збірник матеріалів Міжнародної науково-технічної конференції «ПЕРСПЕКТИВИ ТЕЛЕКОМУНІКАЦІЙ», 2017)
Algorithm for emergency response using wireless sensor networks The use of wireless sensor networks for indoor navigation in emergencies and approaches for emergency response are considered. Direction of further development these algorithm is investigated.